Interjections and Pragmatic Errors in Dubbing - Cuenca, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis paper consists of an analysis of the expressive secondary interjections found in the film Four Weddings and a Funeral and their equivalents in the Spanish and Catalan dubbed versions. The contrastive analysis of the interjections in the original English version compared with the Spanish and the Catalan dubbed versions shows that the strategies followed by the translators are different: literal translation is far more frequent in Spanish than in Catalan. Literal translation often implies an error that is pragmatic in nature since it derives from the misunderstanding of the pragmatic meaning that the interjection conveys.